Amyloid β, Glutamate, Excitotoxicity in Alzheimer's Disease: Are We on the Right Track? - Esposito, Zaira (CNS Neurosci Ther, 2013)
Alzheimer's disease (AD) has a devastating impact on aged people worldwide. Although sophisticated and advanced molecular methods have been developed for its diagnosis since early phases, pharmacological treatment still represents an unresolved topic. The more the disease progresses, the more the uneffectiveness of antidementia drugs emerges. New and encouraging results from experimental works indicate that glutamate pathway may play a substantial role in the pathogenesis since early stages of the disease. Several experimental data together with the clinical use of the uncompetitive N‐methyl‐d‐aspartate (NMDA) antagonist memantine strengthen this idea. Unfortunately, definitive data on the glutamatergic transmission involvement in AD are still incomplete. Moreover, clinical results indicate only temporarily limited effects of memantine. Currently, memantine is indicated for moderate‐to‐severe cases of AD, an indication that may limit its efficacy and impact on Alzheimer's dementia. The association of memantine with the acetylcholinesterase inhibitor drugs used to treat dementia symptoms appears to be beneficial, in both experimental and clinical studies. Because cholinergic and glutamatergic dysfunction occurs early in AD, the coadministration of appropriate treatment in early stages of the disease might represent a valid option from the beginning of cognitive decline. Moreover, to better evaluate drug efficacy, the association of the recently introduced biomarkers with a clinical AD profile should be considered an aim to pursue.